Analysis of gait efficiency and characterization using inertial sensors in treadmill: people with multiple sclerosis - Cabral, Sara Isabel Martins (2022)
Multiple Sclerosis (MS) is an autoimmune disease, with heterogeneous and unpredictable symptoms, from which the gait disorder stands out. The main aim of this study was to explore whether the Inertial Measurement Units (IMUs) allow to identify suble changes in gait parameters in people with Multiple Sclerosis (pwMS) by trying to predict the relationship of the spatiotemporal variables with Modified Borg Scale (MBS) values. It was assessed minimal spatiotemporal abnormalities with reference values. It was analyzed MS variability in a fatigued condition. An observational case control study, included 11 pwMS, while walking for six minutes in a Treadmill, using 15 IMUs to measure 19 spatiotemporal variables and MBS values. It was carried out Shapiro-Wilk test, Spearman’s rank correlation coefficient, one sample T-test and Wilcoxon signed rank test according to the metrics distribution. The level of significance was set at < .05. We found only excellent reliability for two spatiotemporal variables, no correlation between MBS and spatiotemporal variables, and suble differences between IMUs and their reference values. IMUs is a effective instrument to identify suble changes linked to spatiotemporal variables in a group of minimal walking impaired pwMS relapsing-remitting.